Gambaran pencemaran antibiotik pada sistem pembuangan limbah cair di RSUP Prof. Dr. R. D. Kandou Manado - Anggyta Pradifta Kusuma; Dina V. Rombot; Henry M. F. Palandeng (UNIVERSITAS SAM RATULANGI, 2021)
Background : Hospitals in Indonesia produce large amounts of waste water, this can be infectious, contain pathogenic microorganisms and chemicals that are harmful to health and the surrounding environment. Previous studies found antibiotics as one of the ingredients in hospital wastewater, and most of the microorganisms identified from wastewater were reported to be resistant to commonly used antibiotics.Purpose : This study aims to determine the contamination of antibiotics in the wastewater system atÂ RSUP Prof. Dr. R. D. Kandou Manado by doing isolation and bacteria and antibiotic sensitivity tests.Methods: The type of research used is descriptive quantitative research. The sample used is wastewater from the inlet and outlet points. Isolation and bacteria were adjusted according to Bergey's Manual of Determinative Bacteriology. Sensitivity test using Kirby Bauer method with antibiotics used is clindamycin. The results are interpreted based on CLSI.Results: The bacteria that were identified were Bacillus spp., Streptococcus spp., Escherichia spp. and Staphylococcus spp.. These bacteria showed an interpretation of resistance to clindamycin, except for Bacillus spp. which could not be interpreted.Conclusion: Based on the results of the study that the bacteria Streptococcus spp., Escherichia spp. and Staphylococcus spp. which were found to be resistant in the sensitivity test, indicated the presence of antibiotic contamination in the wastewater at RSUP Prof. Dr. R. D. Kandou Manado.Keywords: Hospital waste water, identification of bacteria, sensitivity test